Does The Consumers’ Predictive Accuracy of Inflation Depend on Consumer Income Level? The Case of Poland - Karolina TURA-GAWRON (Communications of International Proceedings, 2025)
The aim of this paper is to recognize and analyze the heterogeneities in accuracy of one year ahead inflation expectations of consumers among different income groups in Poland under the different inflation environments: (1) high inflation environment, (2) low inflation environment, and (3) credible inflation environment. The time span covers May 2001-December 2023. The qualitative EC Business and Consumer Survey inflation expectations have been quantified with the use of Carlson and Parking method adjusted by Batchelorr and Orr. The accuracy of inflation expectations has been analyzed via forecasts errors and verified with the use of HLN test and Diebold-Mariano test. The main conclusion is that the non-credible inflation environment generates heterogeneity in inflation expectations accuracy among the opposite income groups.
Keywords: consumers’ inflation expectations; inflation; income groups; forecast accuracy